OPTIMIZATION OF LEARNING MANAGEMENT SYSTEM BASED ON DIGITAL MODULES IN POST- COVID -19 PANDEMIC DIFFERENTIAL CALCULUS COURSES - Entit Puspita; Ririn Sispiyati; Cece Kustiawan (Jurnal Pengajaran MIPA, 2022)
This study aims to describe the experiences experienced by students regarding optimizing the use of digital module-based LMS in post-pandemic differential calculus lectures. This study's qualitative descriptive method was chosen and involved 46 third-semester students at one of the tertiary institutions in Indonesia who have experienced online and offline classes. Questionnaire and interview data analysis was carried out through identification, clarification, reduction, analysis, and description techniques according to the problem under study. The study results show that the sudden shift from face-to-face to online learning has positive aspects in the form of documentation of lecture activities and presentation of digital-based and varied lecture content. The learning videos were most in demand by the participants because they had advantages over other displays. The weaknesses in implementing online lectures are more technically related (internet or electricity network stability). The positive things detected from online courses can be followed up after the pandemic, especially in the development of LMS content which can be integrated into face-to-face classes